Plants on Islands : Diversity and Dynamics on a Continental Archipelago - Cody, Martin L., 1941- (Book collections on Project MUSE., 2006)
This study examines and critically analyses the island biogeography of plants on continental islands in Barkley Sound and is the result of a quarter-century of research. It discusses isolation and climatic differences and the interplay of coexistence and competition on over 200 islands.